(untitled) (Web of Teachers: Inderscience Research, 2026)
This article is devoted to the study of speech development features in preschool children. The paper analyzes the development of speech, vocabulary, phonetic and morphological skills, as well as the formation of speech culture and communication abilities. The study demonstrates the interrelation between children’s psychological and social development and their speech development. Effective pedagogical methods for fostering speech skills in preschool practice are also suggested.